Integrating Quantitative Data Analytics and Qualitative Insights for Digital Marketing Strategy: A Structural Equation Modeling (SEM) Approach - Suwarno Suwarno; Jhony Susanto; Eryc Eryc (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
The rapid evolution of Batam digital economy presents a paradox: despite high digital channel adoption, many organizations report suboptimal returns on their online investments. This discrepancy highlights a critical research gap: The absence of an integrated, quantitative model that evaluates the collective impact of core data analytics dimensions on strategic performance within this specific context. This study examines how data analytics is pivotal for improving digital marketing outcomes. Adopting a dual-objective approach, it first quantitatively evaluates the effect of five fundamental analytics components on strategic performance, and second, qualitatively uncovers the primary obstacles and facilitators in their application. An explanatory sequential mixed-methods design was employed, commencing with a PLS-SEM analysis of survey data from 150 marketing practitioners in Batam (using a five-point Likert-scale instrument) and concluding with a thematic analysis of qualitative practitioner insights. Empirically, the results validate that all five dimensions (Website Performance, Social Media Metrics, Email Marketing Performance, Customer Data Analysis, and Customer Journey Analysis) significantly enhance the effectiveness of digital marketing strategy. Among these, Customer Journey Analysis was identified as the most powerful determinant (R² = 0.783, Q² = 0.634). The qualitative data elucidated critical implementation barriers such as talent shortages and disconnected data sources, while also highlighting vital success drivers including data-informed personalization. The study’s primary novelty lies in providing a validated, holistic SEM model that establishes the synergistic and hierarchical influence of analytics dimensions, with Customer Journey Analysis as the central pillar. Consequently, it furnishes both a theoretical advancement for scholarly discourse and a practical framework advocating for a strategic reorientation towards holistic customer journey management and the dismantling of data silos to optimize outcomes.